2011
DOI: 10.1017/s0033291711000833
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of suicide risk: a total population study of 11.4 million individuals

Abstract: BackgroundResearch suggests that suicidal behaviour is aggregated in families. However, due to methodological limitations, including small sample sizes, the strength and pattern of this aggregation remains uncertain.MethodWe examined the familial clustering of completed suicide in a Swedish total population sample. We linked the Cause of Death and Multi-Generation Registers and compared suicide rates among relatives of all 83 951 suicide decedents from 1952–2003 with those among relatives of population control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 56 publications
6
141
1
3
Order By: Relevance
“…In line with our findings, the risk of being convicted for a violent crime is also elevated for offspring bereaved of a parent by any cause and regardless of age at loss. 17 Previous research has demonstrated a high level of heritability in suicidal behavior, 32 and, therefore, we adjusted the analyses on suicide for earlier self-harm among parents and children. Likewise, mental disorders have a hereditary component of various degrees for different disorders.…”
Section: Offspring Consequencesmentioning
confidence: 99%
“…In line with our findings, the risk of being convicted for a violent crime is also elevated for offspring bereaved of a parent by any cause and regardless of age at loss. 17 Previous research has demonstrated a high level of heritability in suicidal behavior, 32 and, therefore, we adjusted the analyses on suicide for earlier self-harm among parents and children. Likewise, mental disorders have a hereditary component of various degrees for different disorders.…”
Section: Offspring Consequencesmentioning
confidence: 99%
“…This approach has been previously validated and successfully applied to study other mental disorders and problematic behaviors, such as schizophrenia, 19 bipolar disorder, 19 violent offending, 20 and suicide. 21 As a complementary measure of familial risk, tetrachoric correlations were calculated from the matched data. From this, we estimated additive genetic effects comparing full siblings and maternal half siblings (assuming that they have similar shared environments but 50.0% vs 25.0% genetic similarity on average).…”
Section: Analyses Of Family Datamentioning
confidence: 99%
“…This model did not fit the data significantly better than the full ACE model, thus providing no evidence of qualitative sex differences in the liability for obsessive-compulsive symptoms (P = . 21). Next, we tested for quantitative sex differences by constraining the parameters A, C, and E to be equal across sexes (model 5).…”
Section: Twin Modeling Findingsmentioning
confidence: 99%
“…Several family and twin studies support the notion of higher rates of both completed suicide and suicide attempts in relatives of suicide completers . The familial transmission is not solely dependent on the existence of a psychiatric disorder Tidemalm et al, 2011). Biological, social and psychological factors are all contributing to suicidality within an individual (Caspi et al, 2003;Fu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%